Antibacterial and antibiotic modifying activity of chalcone (2E)-1-(4′-aminophenyl)-3-(4-methoxyphenyl)-prop-2-en-1-one in strains of Staphylococcus aureus carrying NorA and MepA efflux pumps: In vitro and in silico approaches. (August 2022) - Silva, Jacilene; Esmeraldo Rocha, Janaína; da Cunha Xavier, Jayze; Sampaio de Freitas, Thiago; Douglas Melo Coutinho, Henrique; Nogueira Bandeira, Paulo; Rodrigues de Oliveira, Mateus; Nunes da Rocha, Matheus; Machado Marinho, Emanuelle; de Kassio Vieira Monteiro, Norberto; Ribeiro, Lyanna Rodrigues; Róseo Paula Pessoa Bezerra de Menezes, Ramon; et al.
Abstract: A large number of infections are caused by multi-resistant bacteria worldwide, increasing to around 700, 000 deaths per year. Because of that, many strategies are being developed to combat the resistance of microorganisms to drugs, and recently, chalcones have been studied for this purpose. Chalcones are known as α, β-unsaturated ketones, characterized by having the presence of two aromatic rings that are joined by a three-carbon chain. They are a class of compounds considered an exceptional model due to chemical simplicity and a wide variety of biological activities, including anticancer, anti-inflammatory, antioxidants, antimicrobials, anti-tuberculosis, anti-HIV, antimalarial, anti-allergic, antifungal, antibacterial, and antileishmaniasis. The objective of this work was to evaluate the antibacterial and antibiotic modifying activity of chalcone ( 2E )-1-(4′-aminophenyl)-3-(4-methoxyphenyl)-prop-2-en-1-one against the bacteria Staphylococcus aureus carrying a NorA and MepA efflux pump. The results showed that chalcone showed no toxicity on macrophage cells and was able to synergistically modulate the action of Norfloxacin and Ethidium Bromide against the bacteria Staphylococcus aureus 1199B and K2068, respectively. Furthermore, the theoretical physicochemical and pharmacokinetic properties of chalcone showed that it did not present a severe risk of toxicity such as genetic mutation or cardiotoxicity, constituting an excellent pharmacological active ingredient. Graphical abstract: Image 1 Highlights: Chalcone modula sinergicamente a ação da Norfloxacina contra as bactérias Staphylococcus aureus 1199B. Chalcone modula sinergicamente a ação da o Brometo de Etídio contra as bactérias Staphylococcus aureus 1199B. Farmacocinetica preditva indica que a chalcon não apresenta risco grave de toxicidade. Chalcona possui energia de afinidade mais favorável Pela Nor que o Norfloxacina.